Research on the recommendation strategy of dual-channel manufacturers for hybrid e-commerce platforms - Wang, Yang (Frontiers in Physics, 2024)
IntroductionIn the context of hybrid e-commerce platforms with reselling mode and agency mode, this study considers the issue of channel management by manufacturers through recommendation strategies.MethodsFor three dual-channel structures composed of e-commerce platforms, manufacturers, and third-party retailers, game models were constructed for manufacturer’s non-recommendation, differentiated recommendation, and indiscriminate recommendation scenarios to investigate the optimal recommendation strategy for manufacturers.Conclusion(1) For different dual-channel structures, compared to scenarios without recommendations, it is not always profitable for manufacturers to adopt a recommendation strategy as recommended parties may not necessarily gain higher profits from recommendations. (2) The optimal recommendation strategy for manufacturers is influenced by channel structure, commission rates, and relative scale in the recommended market. Recommending direct sales channels is the preferred choice for manufacturers with a higher relative scale in the recommended market prompting them to recommend all channels to consumers. (3) Numerical simulations reveal that retail prices, total market demand, and supply chain profits are positively correlated with relative scale within the recommended market. Additionally, any recommendation strategy can increase demand for recommended parties as well as overall supply chain profit levels.